The politics of appropriation : German romantic music and the ancient Greek legacy - Geary, Jason (New cultural history of music., 2014)
This text explores the intersection of music and Hellenism in 19th-century Germany. It shows how productions such as that of the Prussian court of Sophocles' Antigone with music by Felix Mendelssohn reflect an effort by the rulers who commissioned them to appropriate the legacy of Greece for the creation of a German cultural and national identity.